CEVÂMİ'Ü'L-HİKÂYÂT VE LEVÂMİ'Ü'R-RİVÂYÂT TERCÜMESİ (2, 3 VE 4. KISIMLAR) (İNCELEME-METİN) - BATAR, KÜBRA (Fırat Üniveristesi, 2022)
Cevâmiü'l-hikâyât ve Levâmi'ü'r-rivâyât 13. yüzyılda İranlı yazar Muhammed Avfî tarafından yazılan Farsça bir eserdir. Dinî, ahlâkî, tarihî, menkıbevî ve mitolojik hikâyelerin anlatıldığı eserde 2000'den fazla hikâye mevcuttur. Kaynaklara göre eserin edebiyatımıza kazandırılan üç tercümesi bulunmaktadır. İbn Arabşah, Necâtî ve Celâlzâde Salih Çelebi tarafından gerçekleştirilen bu tercümelerden günümüze kadar ulaşabilen Celâlzâde tercümesi olmuştur. İbn Arabşah ve Necâtî tercümelerine ise rastlanmamıştır. Çalışmamızın konusunu teşkil eden Hasan Paşa Yazma Eser Kütüphanesi, Hasan Hüsnü nr. 720 kayıtlı Cevâmiü'l-hikâyât ve Levâmi'ü'r-rivâyât tercümesinin Necâtî'ye ait olduğuna yönelik görüşler bulunsa da tercümenin incelediğimiz kısımlarında buna dair bir bilgiye rastlanmamıştır. Nüshadaki istinsah kaydına göre eser, Aralık 1539'da yazılmıştır. Bu çalışmada Hasan Paşa Yazma Eser Kütüphanesi, Hasan Hüsnü nr. 720 kayıtlı Cevâmiü'l-hikâyât ve Levâmi'ü'r-rivâyât'ın 2, 3 ve 4. kısımlarının çeviri yazısı yapılmış, devamında eserin muhtevası, tahkiye unsurları ile dil ve üslup özellikleri üzerinde durulmuştur.

Cevâmi'ü'l-hikâyât and Levâmi'ü'r-rivâyât are Persian workswritten by Iranian writer Muhammed Avfî in thirteenth century. There are more than 2000 stories in the work in which religious, moral, historical, epical and mythological stories are told. According to the sources, there are three traslations of the work brought to our litarature. Among these translations made by Ibn Arabşah, Necati and Celalzâde Salih Çelebi there has been Celalzâde's translation that has survived to the present day. The translations of Ibn Arabşah and Necati could not be reached. Although there are opinions that the traslations of Cevâmiü'l-hikâyât and Levâmi'ü'r-rivâyât which are recorded in Hasan Paşa Manuscript Library nr. 720-that is the subject of our study belongs to Necati, we did not find any information about this in the parts of the translation that we examined. According to the copying record the work was written in December 1539. In this study, Hasan Pasha Manuscript Library, Hasan Hüsnu nr.720, the 2nd, 3rd and 4th parts of the recorded Cevâmiü'l-hikâyát and Levami'ü'r-rivâyát are translated. In addition, the content of the work, the elements of narration, and the language and style features are emphasized.
Translation of Cevâmi'ü'l-Hikâyât and Levâmi'ü'r-Rivâyât(2, 3 and 4. sections) (Examination-text)
Keywords: Türk Dili ve Edebiyatı; Doğu Dilleri ve Edebiyatı